Genetic heterogeneity of Escherichia coli isolated from pasteurized milk in State of Paraná, Brazil - Karine Oltramari; Rosilene Fressati Cardoso; Eliana Valéria Patussi; Adolfo Carlos Barreto Santos; Jane Martha Graton Mikcha (Universidade de São Paulo, 2014)
Food contamination caused by enteric pathogens is a major cause of diarrheal disease worldwide, resulting in high morbidity and mortality and significant economic losses. Bacteria are important agents of foodborne diseases, particularly diarrheagenic Escherichia coli. The present study assessed the genetic diversity and antimicrobial resistance of E. coli isolates from pasteurized milk processed in 21 dairies in northwestern State of Parana, Brazil. The 95 E. coli isolates were subjected to antimicrobial susceptibility testing according to the recommendations of the Clinical and Laboratory Standards Institute and assessed genotypically by Enterobacterial Repetitive Intergenic Consensus-Polymerase Chain Reaction (ERIC-PCR). The highest rate of resistance was observed for cephalothin (55.78%). ERIC-PCR revealed high genetic diversity, clustering the 95 bacterial isolates into 90 different genotypic patterns. These results showed a heterogeneous population of E. coli in milk samples produced in the northwestern region of Paraná and the need for good manufacturing practices throughout the processing of pasteurized milk to reduce the risk of foodborne illnesses.